The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1111/j.1432-1033.1991.tb16239.x
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescence spectroscopic study of glutaminyl‐tRNA synthetase from Escherichia coli and its implications for the enzyme mechanism

Abstract: Interaction between Escherichia coli glutaminyl-tRNA synthetase (GlnRS) and its substrates have been studied by fluorescence quenching. In the absence of other substrates, glutamine, tRNAG'" and ATP bind with dissociation constants of 460, 0.22 and 180 pM, respectively. The presence of other substrates has either no effect or, at best a weak effect, on binding of ligands. Attempts to isolate enzyme-bound aminoacyl adenylate did not succeed. Binding of the phosphodiester, 5'-(methy1)adenosine monophosphate (MeA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 38 publications
7
46
1
Order By: Relevance
“…Thus, we have measured tRNAG'" binding to GlnRS by quenching of the tryptophan fluorescence. Previously we have shown that binding of tRNAG1" leads to significant quenching of tryptophan fluorescence (Bhattacharyya et al, 1991). to the GlnRS/ATP complex reported here is in contrast to approximately 300-fold difference in binding constant in the absence of ATP reported by Weygand-Durasevic et al (1993), suggesting a strong ATP effect and possibly ordered substrate binding.…”
Section: Resultscontrasting
confidence: 78%
See 3 more Smart Citations
“…Thus, we have measured tRNAG'" binding to GlnRS by quenching of the tryptophan fluorescence. Previously we have shown that binding of tRNAG1" leads to significant quenching of tryptophan fluorescence (Bhattacharyya et al, 1991). to the GlnRS/ATP complex reported here is in contrast to approximately 300-fold difference in binding constant in the absence of ATP reported by Weygand-Durasevic et al (1993), suggesting a strong ATP effect and possibly ordered substrate binding.…”
Section: Resultscontrasting
confidence: 78%
“…Enzyme assays are also described in the same article. The protein preparation showed a single band on SDS polyacrylamide gel and had specific activity comparable to those reported in Bhattacharyya et al (1991).…”
Section: Enzyme Purificationsupporting
confidence: 74%
See 2 more Smart Citations
“…Alternatively, the aaRS can be chemically modified by derivatization with an extrinsic probe that is sensitive to local chemistry, thereby serving as a reporter of local changes in structure. The extrinsic probes employed include those that interact with the protein non-covalently, such as 5′,5′-bis(8-anilino-1-naphthalene sulfonate [67] and AF-tetrafluorophenylester [68], or those that can be covalently linked to exposed cysteines by maleimide chemistry [69]. Alternatively, if the labeling of the protein is not feasible, methods have been described for the extrinsic labeling of the 5′-terminus of the tRNA with a fluorophore [70,71].…”
Section: Fluorescence Approaches To Studying Adenylation and Aminoacymentioning
confidence: 99%